THE RELATIONSHIP BETWEEN EMOTIONAL AND AFFECTIVE DISORDERS AND COGNITIVE STATUS IN CHRONIC CEREBROVASCULAR PATHOLOGY (World Bulletin of Public Health, 2025)
Chronic cerebrovascular pathology is one of the leading causes of cognitive impairment in people over 50 years of age. The combination of cognitive dysfunction with emotional and affective disorders can significantly affect the course of the disease and the quality of life of patients, which determines the importance of studying their relationship.